THE STRATEGY AND COHERENCE OF READING TEXTS IN OPTIMIZING THE CHILD AWARENESS ON SOCIAL ENVIRONMENT - Vilya Lakstian Catra Mulia (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
English Each text genre has their own social function to fulfill the purpose of reading activities, therefore texts serve as an inseparable medium of learning in schools. This study explores the function and purposes of texts in correlation of recent social issues in the society. The data includes textbooks from the most recent curriculum. The data was analyzed into some phases of each genre based on Islamic perspectives. Social literacy is essentially needed since early ages of the children to equip them with the knowledge of socializing. In this case, texts are expected to be internalized by the children in their surrounding social environment. Besides exploring the text genres, this study also formulates some suggestions for the development of texts as well as for the teachers who communicate the content of the texts to the students. Indonesia Setiap genre teks memiliki fungsi sosialnya masing-masing untuk memenuhi tujuan dari aktifitas membaca. Oleh karena itu, teks menjadi media pembelajaran yang tidak bisa dipisahkan dari kegiatan belajar di sekolah. Berkaitan dengan fungsi dan tujuan dari teks yang lebih luas, penulis mengaitkannya dengan permasalahan sosial terkini di masyarakat dengan sumber data dari buku kurikulum terbaru. Literasi sosial diperlukan sejak dini untuk memberikan bekal pengetahuan bermasyarakat sehingga manfaat teks diharapkan dapat diinternalisasikan oleh anak-anak terhadap lingkungan sosial di sekitarnya. Selain mengeksplorasi genre teks pada sumber data, penulis juga berusaha memberikan saran pengembangan bagi teks maupun kepada guru sebagai pihak yang berperan penting sebagai penghubung berbagai aspek yang dibawa teks kepada para siswanya. Penulis memperoleh temuan tersebut melalui analisis pentahapan dari setiap genre dan sudut pandang Islami.